Polineuropatia associada a hipotireoidismo em cães: Relato de seis casos - Suraniti, Adriana Patricia; Gilardoni, Liliana Rosa; Rama Llal, Mabel Graciela; Echevarría, Marcelo; Marcondes, Mary [UNESP] (My University, 2008)
Six Doberman Pinscher, between six and eight years of age, were presented to the Veterinary Hospital from Faculty of Veterinary Science of The University of Buenos Aires. Neurological examination revealed tetraparesis with inability to walk, decreased muscle tonus and myotatic reflexes in all dogs. Serum cholesterol levels, creatine kinase and alkaline phosphatase activities were mildly to markedly elevated, and tibial motor nerve conduction velocities were slow in all dogs. Basal measurements of free T4 and TSH were determined by radioimmunoassay. Although fT4 values were within normal range, in all dogs TSH values were elevated. Based on this results, hypothyroidism was diagnosed and a supplementation therapy was established with oral levothyroxine (T4). Two weeks after treatment has been started, all patients had an improvement in clinical signs, and within a month gait became normal, as well as muscular tonus and spinal reflexes.
Hypothyroid associated polyneuropathy in dogs: Report of six cases
Keywords: Motor nerve conduction velocity; Neuropathy; Thyroid hormones; Canis familiaris